2016
DOI: 10.1111/bjh.14240
|View full text |Cite
|
Sign up to set email alerts
|

Detection of prognostic factors in children and adolescents with Burkitt and Diffuse Large B‐Cell Lymphoma treated with theAIEOP LNH‐97 protocol

Abstract: SummaryBurkitt lymphoma (BL) and Diffuse Large B-Cell Lymphoma (DLBCL) account for most cases of non-Hodgkin lymphoma (NHL) in childhood. We report the clinical characteristics, outcome and prognostic factors in children with BL or DLBCL treated according to the Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) LNH-97 protocol. Patients aged up to 18 years that were newly diagnosed with BL/DLBCL were included in the study. Therapy consisted of pre-phase followed by 2-6 high-dose chemotherapy course… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…Finally, in a larger study including 422 patients (379 BL), in the subgroup of 128 children and adolescents who had the study done, MDD was the only risk factor in multivariate analysis. Studies from the Children’s Oncology Group yielded nearly similar results 54. A report on 14 BL subjects showed that none of 12 MRD-negative after 2 months of therapy relapsed compared to both those found MRD-positive 55.…”
Section: Minimal Disseminated and Residual Diseasementioning
confidence: 77%
See 1 more Smart Citation
“…Finally, in a larger study including 422 patients (379 BL), in the subgroup of 128 children and adolescents who had the study done, MDD was the only risk factor in multivariate analysis. Studies from the Children’s Oncology Group yielded nearly similar results 54. A report on 14 BL subjects showed that none of 12 MRD-negative after 2 months of therapy relapsed compared to both those found MRD-positive 55.…”
Section: Minimal Disseminated and Residual Diseasementioning
confidence: 77%
“…Apart from stage, these were an elevated LDH, primary mediastinal involvement, and combined bone marrow/CNS disease 37. The pediatric Italian review on 379 BL patients confirmed LDH to exert the greatest prognostic relevance ( P <0.0001) 54. Among biomarkers, apart from MDD/MRD which is not always available, some specific cytogenetic findings, such as deletion of 13q, gain of 7q, and complex cytogenetics, could impart a worse prognosis and/or benefit from treatment intensification 37.…”
Section: Other Clinical and Biological Risk Factorsmentioning
confidence: 97%
“…Since 1997, patients with B‐NHL have been enrolled in the NHL‐BFM based, AIEOP LNH‐97 protocol . However, based on the reported inferior outcome of patients with PMLBL compared to other B‐NHL histological subtypes treated in the NHL‐BFM trials (EFS 70% vs. 84%), from 2007 the AIEOP‐NHL committee recommended to treat PMLBL according to a modified version of AIEOP LNH‐97.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, all patients received six doses at 375 mg/m 2 of anti‐CD20, rituximab. Central nervous system (CNS) prophylaxis was given according to AIEOP LNH‐97 protocol . Evaluation of response was scheduled after each chemotherapy course until complete remission (CR) was obtained (defined as absence of any residual disease) by performing procedures positive for disease at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation